MENINGKATKAN MINAT BELAJAR SISWA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN EXAMPLE NON EXAMPLE PADA MATA PELAJARAN IPA MATERI ORGAN GERAK HEWAN DI KELAS V MI CAHAYA KOTA CIMAHI - ERNI KUSMIAT; WINI GANTINI (EDUCATOR : Jurnal Inovasi Tenaga Pendidik dan Kependidikan, 2023)
This study aims to find out: First, students' interest in learning before using the Examples Non Examples learning model in Natural Sciences subject of Animal Motion Materials in class 5 MI Cahaya. Second, the learning process by using the Examples Non Examples learning model in Natural Sciences subject of Animal Motion Organs in class 5 MI Cahaya. Third, students' interest in learning after using the Examples Non Examples learning model in Natural Sciences subject of Animal Motion Organs in class 5 MI Cahaya. This research uses descriptive method of Classroom Action Research model. Data collection techniques using interviews, observation, tests, questionnaires and documentation. The conclusion of this study is first, the interest in learning in class V Al-Kahfi is moderate, it is in accordance with the results of the pre-cycle data that is the student learning interest questionnaire obtained ie the average student answers the most frequently namely 44%, sometimes sometimes 47% and never 9%. This is consistent with the results of the interview that students' interest in learning before using the Example Non Example model that is being the same as the results of the most average questionnaire at sometimes that is 47%. Second, the learning process is carried out in two cycles, each cycle consisting of four stages namely planning, action, observation and reflection. Third, after the research process was implemented there was an increase starting from the average written test results of the first cycle to the second cycle of 4.6%, for an increase in the average performance of the first cycle to the second cycle 12.1%. For the results of observations of student activities in the first cycle that is 82.1% and in the second cycle to 88.9% and the results of observations of the activities of teachers in the first cycle 94.8% in the second cycle to 100%. ABSTRAKPenelitian ini bertujuan untuk mengetahui: Pertama, minat belajar siswa sebelum menggunakan model pembelajaran Examples Non Examples pada mata pelajaran IPA Materi Organ Gerak Hewan dikelas 5 MI Cahaya. Kedua, proses pembelajaran dengan menggunakan model pembelajaran Examples Non Examples pada mata pelajaran IPA Materi Organ Gerak Hewan dikelas 5 MI Cahaya. Ketiga, minat belajar siswa setelah menggunakan model pembelajaran Examples Non Examples pada mata pelajaran IPA Materi Organ Gerak Hewan dikelas 5 MI Cahaya. Penelitian ini menggunakan metode deskriptif model Penelitian Tindakan Kelas (PTK). Teknik pengumpulan data menggunakan wawancara, observasi, tes, angket dan dokumentasi. Kesimpulan dari penelitian ini adalah pertama, Minat belajar pada siswa kelas V Al-Kahfi itu sedang, hal tersebut sesuai dengan hasil dari data pra siklus yaitu angket minat belajar siswa yang diperoleh yaitu rata-rata siswa paling banyak menjawab sering yaitu 44 %, kadang-kadang 47 % dan tidak pernah 9 %. Hal tersebut sesuai dengan hasil wawancara bahwa minat belajar siswa sebelum menggunakan model Example Non Example yaitu sedang sama seperti hasil angket rata-rata terbanyak pada kadang-kadang yaitu 47 %. Kedua, proses pembelajaran dilaksanakan dalam dua siklus, setiap siklus terdiri dari empat tahap yaitu perencanaan, tindakan, observasi dan refleksi. Ketiga, setelah dilaksanakan proses penelitian tersebut adanya peningkatan dimulai dari rata-rata hasil tes tertulis siklus I ke siklus II 4.6%, untuk peningkatan rata-rata hasil unjuk kerja kelompok siklus I ke siklus II 12.1%. Untuk hasil observasi aktivitas siswa pada siklus I yaitu 82.1% dan pada siklus II menjadi 88.9% dan hasil observasi aktivitas guru pada siklus I 94.8% pada siklus II menjadi 100%.